f(2)=4(2)+6

Simple and best practice solution for f(2)=4(2)+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(2)=4(2)+6 equation:


Simplifying
f(2) = 4(2) + 6

Reorder the terms for easier multiplication:
2f = 4(2) + 6

Multiply 4 * 2
2f = 8 + 6

Combine like terms: 8 + 6 = 14
2f = 14

Solving
2f = 14

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Divide each side by '2'.
f = 7

Simplifying
f = 7

See similar equations:

| 21/2h-3/4=11/2 | | 7+1x=4 | | f(3)=4(3)+6 | | 1a^2-28a+192=0 | | 10D+5N=185 | | 5x+1=-2x+1 | | 8x-11x-22=-6 | | 3a-11/2=-51/4 | | 9ab^2= | | 2u-27=u | | 5+-2(x+-1)=2(3+4x)+7 | | 155/9 | | (2y-y)/(2x-5x) | | -4(3n-2)-n=11(n-1) | | 7p+22=10p-80 | | 3x+15=7x | | F(x)=3x^2-5x-4 | | -9(6+4k)=23 | | x+35=130 | | x-5x^2= | | d=mb+gaforb | | f(3)=4g+6 | | (3f+6)(2f-4)=0 | | -12n-n=11n-1 | | 5y-8=5y-8 | | F(x)=2x^2+6x+5 | | 7v-17=v+7 | | 6x+20=98 | | 3x+10=8x+15 | | -16t^2-10t+3=0 | | 5x+7=130 | | 7b-66=b |

Equations solver categories